Heterogeneity of Cultured Melanocyte Elongation and Proliferation Factor in Bilateral Diffuse Uveal Melanocytic Proliferation - Lavine, Jeremy A. (Exp Eye Res, 2019)
A patient with bilateral diffuse uveal melanocytic proliferation (BDUMP) associated with endometrial cancer was treated with plasmapheresis, but failed therapy with progressive serous retinal detachment. We collected plasma before and after plasmapheresis therapy. Our goal was to determine if the cultured melanocyte elongation and proliferation (CMEP) factor and hepatocyte growth factor (HGF) was present in the IgG enriched fraction and understand why our patient failed plasmapheresis therapy. Melanocytes were cultured for 3-5 days in the presence of control medium, unfractionated pre-plasmapheresis BDUMP medium, IgG enriched or IgG depleted BDUMP medium, or unfractionated post-plasmapheresis BDUMP medium. Subretinal fluid was collected from patients with BDUMP and control retinal detachments and analyzed by electropheresis with immunoblotting. Medium with unfractionated BDUMP plasma stimulated melanocyte growth 1.4-1.5 fold compared to control medium on days 3-5 (p < 0.001 for all). Both IgG enriched and IgG depleted BDUMP medium mildly increased melanocyte growth 1.3 fold (p < 0.05 for enriched, p < 0.01 for depleted) compared to control. In comparison, unfractionated BDUMP medium caused a 1.7-fold increase in melanocyte growth, which was significantly more than the enriched (p < 0.01) and depleted (p < 0.05) fractions. Pre-plasmapheresis and post-plasmapheresis unfractionated BDUMP medium equally stimulated melanocyte growth 1.7-fold (p < 0.05) compared to control. HGF was present in IgG depleted, pre-plasmapheresis, and post-plasmapheresis samples, but absent in the IgG enriched fraction. There was no enrichment of IgG in the subretinal fluid from eyes with BDUMP. In conclusion, CMEP factor is not concentrated in the IgG enriched plasma fraction in our patient who failed plasmapheresis therapy. HGF levels have no correlation with melanocyte growth. Because plasmapheresis preferentially removes immunoglobulins from the plasma, our patient responded poorly to plasmapheresis treatment with worsening retinal detachment.